The Family Hope Program (PKH) Collective Partnership among Beneficiary Families (KPM) For Healthy Living through the Clean Friday Campaign - Umi Faridav; Misnawati; Juharbi; Mariadi; Yusriadi Yusriadi; Amar Saniv (Institute of Medico-legal Publications Pvt Ltd, 2021)
Concerning the importance of collective partnership, to encourage a Safe and Balanced Way of Life,PKH Facilitators in Bone District, South Sulawesi, carry out the Clean Friday Campaign initiative as acollective partnership in enforcing a sanitation or cleaning program for the village by including all KPMPKH. This paper explains what the Clean Friday Campaign is, how PKH facilitators inspire KPM PKH Thestudy site was situated in the Bone Regency, South Sulawesi Province of the Cina District. Interviews andfindings, and documentation were carried out as data collection procedures, which were then analyzed byMiles and Huberman using research theory. The study’s findings show that every Friday morning, the CleanFriday Campaign is carried out every week towards public facilities guided by the collaboration of PKHFacilitators with village and sub-district governments to increase the self-awareness of KPM in ensuring asafe atmosphere for a safe and stable existence.